A Head-to-Head Comparison of the Vascular Basis of the Transverse Myocutaneous Gracilis, Profunda Artery Perforator, and Fasciocutaneous Infragluteal Flaps: An Anatomical Study. Issue 2 (February 2019) - Zaussinger, Maximilian; Tinhofer, Ines E.; Hamscha, Ulrike; Meng, Stefan; Weninger, Wolfgang J.; Pollhammer, Michael S.; Huemer, Georg M.; Schmidt, Manfred
Abstract : Background: Perforator flaps of the upper thigh or buttock provide a valuable secondary choice in autologous breast reconstruction. The purpose of this study was to compare the vascular territories and supplying vessels of the transverse myocutaneous gracilis flap, the profunda artery perforator flap, and the fasciocutaneous infragluteal flap. Methods: In total, 26 lower limbs from 13 fresh specimens were investigated. All flap pedicles were selectively injected with methylene blue, eosin red, or green ink. The pedicle external diameters, lengths, and locations were measured. The dimensions of angiosomes, their intraindividual and interindividual correlations, and their relations to anatomical landmarks were analyzed. Results: The profunda artery perforator pedicle had the greatest mean external diameter with 3.6 ± 0.7 mm, followed by the transverse myocutaneous gracilis and fasciocutaneous infragluteal pedicles with 2.9 ± 0.6 mm and 2.9 ± 0.7 mm, respectively. The fasciocutaneous infragluteal pedicle was longest with a mean length of 12.5 ± 1.5 cm, whereas the profunda artery perforator and transverse myocutaneous gracilis pedicles had lengths of 8.8 ± 1.0 cm and 6.7 ± 1 cm on average. The profunda artery perforator angiosome provided the largest size, with a mean area of 98.5 ± 26.7 cm 2, followed by the fasciocutaneous infragluteal angiosome (77.2 ± 9.0 cm 2 ) and the transverse myocutaneous gracilis angiosome (74.1 ± 32.1 cm 2 ). Conclusions: The authors' anatomical findings about the transverse myocutaneous gracilis, profunda artery perforator, and fasciocutaneous infragluteal territories provide clinically valuable data for flap selection in breast reconstruction if an abdominal flap is not feasible.